Analysis of the schema defined integral of a university student (Revista de Investigaciones Universidad del Quindío, 2021)
This article describes the development of the scheme of the Definite Integral concept of a university student who deals the third year of Bachelor of Mathematics. This is the first time he studies this mathematicol concept. In this research, initial/y was done a textbooks review to identify the mathematical elements that form the Definite Integral concept. This allowed us to deslgn its genetic decomposition. To gather data, firstly a pilot questionnaire was applied, and then three definitive instruments were constructed: a questionnaire, an interview and a conceptual map. The analysis of the data was done identifying the mathematica/ elements that the student used to so/ve the different tasks, the logical relations estoblished between these mathematical elements and the use of different systems of representation like graphical, algebraic and analytical systems of representation. The results of the analysis allowed us to characterize íts leve/ of development of the conceptual scheme related to the Definite Integral concept.
Keywords: Definíte Integral; development of the scheme; mathematical element; genetic decomposition